الضمانات الإجرائية الجنائية للمتهم في القانون العماني والشريعة الإسلامية - جهضمي، محمود بن حامد بن سيف (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2015)
As the dissertation title implies, this study aims at an attempt to probe, analyse and explain the procedural criminal safeguards given to an accused at the investigation stage and during the trial before Omani Law through a comparison between the Omani Law and the Shari'ah. This is to find out to what extent the two systems have reached in addressing this most important issue at the national and international levels as a valuable addition to the ultimate goal of establishing an integrated jurisdiction system in Oman. The study is based on setting out the rights and liberties guaranteed by the Omani Criminal Procedure Law. The rationale behind selecting these assurances as the starting point of this research is that they are construed to be a bedrock of any judiciary, being a source of protection stemming from the principle of procedural criminal legitimacy which consists of the umbrella legislature where most of the provisions dealing with the protection of the accused are found, and with the explanatory legal articles needed for affording such assurances. The focus of this dissertation is the Omani procedural criminal and judiciary protections which provide for the accused culminating in a comparison with the Shari'ah. To further enrich the discussion, pertinent rules and regulations applied in other laws have also been cross-referenced, whenever deemed necessary. The objective is to try to ascertain whether or not both legal regulations governing the procedural criminal and judiciary application aspects in the Sultanate of Oman conform with the standards of procedural assurances in the Shari'ah, and how to fill any procedural gap, if any. Despite the efforts of the Omani legislators, the additional rules and procedures for this issue still need to be applied. Recommendations and suggestions for the development of the safeguards in the Omani law and judiciary applications are included.